Anti-racist and anti-colonial content within US global health curricula. - Sanemba Aya Fanny; Amy Rule; Heather L Crouse; James C Hudspeth; Bethany Hodge; Marideth Rus; Heather Haq (PLOS Global Public Health)
There is a growing interest to address pervasive racist and colonialist practices in global health (GH). However, there is a paucity of information on anti-racist and anti-colonial (ARAC) education for GH trainees. This study aimed to identify curricular strengths and gaps in ARAC content for pediatric, family medicine and emergency medicine trainees participating in GH. We conducted a cross-sectional survey of GH programs' ARAC curricular content from May 2021 to January 2022. The survey was distributed to 148 GH program educational leaders via email. Descriptive statistics were used to describe quantitative data and comments were reviewed for common themes. The survey response rate was 44% (n = 65). The most represented programs were pediatric residency GH tracks (n = 24, 37%) and emergency medicine (n = 13, 20%), family medicine (n = 4, 6%) and pediatric emergency medicine (n = 6, 9%) GH fellowships. 28% of programs (n = 18) did not have faculty who identify as underrepresented minorities or international medical graduates. 56 programs (86%) had a formal GH pre-departure curriculum. The following areas were the least covered in respondents' curricula: anti-racism (n = 34, 53%), white saviorism (n = 34, 53%), history of GH (n = 24, 37.5%). 63% (n = 40) had bidirectional exchanges of trainees or faculty, but often with significant limitations. While most GH programs recognized the need for formal pre-departure training prior to international experiences, we identified a lack of diversity among GH faculty, significant areas for improvement in curricular content, and a need for more robust bi-directional partnerships. A more equitable future in GH hinges on addressing these educational gaps.